Gas release mitigation in LiFePO4-Li4Ti5O12 Li-ion pouch cells by an H2-selective getter. (20th January 2019) - Zilio, Stefano; Manzi, Jessica; Fernicola, Alessandra; Corazza, Alessio; Brutti, Sergio
Abstract: In this work we discuss the mitigation of H2 accumulation upon cycling within a Li-ion battery (LIB) by the use of an hydrogen selective getter (i.e. Suisorb™). This getter has been tested in electrochemical cells constituted by a Li4 Ti5 O12 (LTO) negative electrode material, a LiFePO4 (LFP) positive electrode material and a common liquid electrolyte (1 M solution of LiPF6 ethylene carbonate/dimethyl-carbonate) absorbed on a Celgard separator. LTO and LFP electrode performance has been analysed in lithium half cells and in full Li-ion configurations by galvanostatic cycling. The gas release within the LIB, assembled without and with the insertion of the getter, has been studied by electrochemical pressure tests to monitor the internal pressure within the cell and by gas chromatography to study the speciation of the gas. The modification of the electrode surface composition has been analysed by photoemission spectroscopy and the alteration in the morphology of the aluminium counter-collectors by electron microscopy. The incorporation of the Suisorb™ getter within LTO/LFP LIBs mitigates the accumulation of molecular hydrogen upon cycling, limits the LiPF6 hydrolysis and LiF formation and decreases the aluminium counter-collector pitting corrosion upon cycling. Furthermore also the battery performance are enhanced by the use of Suisorb™. Highlights: Suisorb™ has been used within a LTO/LFP Li-ion battery as selective getter for H2 . The limitation of the H2 accumulation upon cycling improves the battery performance. The degradation chemistry occurring upon cycling is modified by the capture of gaseous hydrogen.